Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(x^3+x^2-2x+a⋮x+1\)
\(\Leftrightarrow x^3+x^2-2x-2+a+2⋮x+1\)
=>a+2=0
hay a=-2
b: \(2x^3-4x^2-3a⋮2x-3\)
\(\Leftrightarrow2x^3-3x^2-x^2+1.5x-1.5x+2.25-3a-2.25⋮2x-3\)=>-3a-2,25=0
=>-3a=2,25
hay a=-0,75
c: \(4x^4+3x^2-ax+3⋮x+3\)
\(\Leftrightarrow4x^4+12x^3-12x^3-36x^2+39x^2+117x-ax+3⋮x+3\)
\(\Leftrightarrow-ax+3⋮x+3\)
\(\Leftrightarrow-ax-3a+3+3a⋮x+3\)
=>3a+3=0
hay a=-1
a) Ta có : (x - 5)2 - 16
= (x - 5)2 - 42
= (x - 5 - 4)(x - 5 + 4)
= (x - 1)(x - 9)
b) 25 - (3 - x)2
= 52 - (3 - x)2
= (5 - 3 + x)(5 + 3 - x)
= (x + 2)(8 - x)
c) (7x - 4)2 - (2x + 1)2
= (7x - 4 - 2x - 1)(7x - 4 + 2x + 1)
= (5x - 5)(9x - 3)
= 5(x - 1)3(3x - 1)
= 15(x - 1)(3x - 1)
TA CÓ:
\(a,\left(4x-1\right)\left(x-3\right)=\left(x-3\right)\left(5x+2\right)\Leftrightarrow\left(4x-1\right)\left(x-3\right)-\left(x-3\right)\left(5x+2\right)=0\)
\(\left(x-3\right)\left(4x-1-5x-2\right)=0\Leftrightarrow\left(x-3\right)\left(-x-3\right)=0\orbr{\begin{cases}x=3\\x=-3\end{cases}}\)
\(b,\left(x+3\right)\left(x-5\right)+\left(x+3\right)\left(3x-4\right)=0\Leftrightarrow\left(x+3\right)\left(x-5+3x-4\right)=0\)
\(\left(x-3\right)\left(4x-9\right)=0\orbr{\begin{cases}x=3\\x=\frac{9}{4}\end{cases}}\)
\(c,\left(1-x\right)\left(5x+3\right)=\left(3x-7\right)\left(x-1\right)\Leftrightarrow\left(1-x\right)\left(5x+3\right)=\left(7-3x\right)\left(1-x\right)\)
\(\left(1-x\right)\left(5x+3-7+3x\right)=0\Leftrightarrow\left(1-x\right)\left(8x-4\right)=0\orbr{\begin{cases}x=1\\x=\frac{1}{2}\end{cases}}\)
a) a2(a-b)-b2(a-c)-c2(b-a)
=a2(a-b)-b2(a-c)+c2(a-b)
=(a-b)(a2-c2)-b2(a-c)
=(a-b)(a-c)(a+c)-b2(a-c)
=(a-c)[(a-b)(a+c)-b2]
b)a(b-c)3+b(c-a)3+c(a-b)3
=a(b-c)3-b[(a-b)+(b-c)]+c(a-b)3
=a(b-c)3-b[(a-b)3+3(a-b)2(b-c)+3(a-b)(b-c)2+(b-c)3]+c(a-b)3
=a(b-c)3-b(a-b)3+3b(a-b)2(b-c)+3b(a-b)(b-c)2+b(b-c)3+c(a-b)3
=(b-c)3(a-b)-(a-b)3(b-c)-3b(a-b)(b-c)(a-b+b-c)
=(b-c)3(a-b)-(a-b)3(b-c)-3b(a-b)(b-c)(a-c)
=(a-b)(b-c)[(b-c)2-(a-b)2-3b(a-c)]
=(a-b)(b-c)[(b-c-a+b)(b-c+a-b)-3b(a-c)]
=(a-b)(b-c)[(2b-a-c)(a-c)-3b(a-c)]
=(a-b)(b-c)(a-c)(2b-a-c-3b)
=-(a-b)(b-c)(a-c)(a+b+c)
=(a-b)(b-c)(c-a)(a+b+c)
c)abc-(ab+ac+bc)+(a+b+c)-1
=abc-ab-ac-bc+a+b+c-1
=abc-bc-ab+b-ac+c+a-1
=bc(a-1)-b(a-1)-c(a-1)+a-1
=(a-1)(bc-b-c+1)
=(a-1)[b(c-1)-(c-1)]
=(a-1)(c-1)(b-1)
=(a-1)(b-1)(c-1)
\(\left(a+b\right)^2=a^2+2ab+b^2\)2
\(\left(a+b\right)^2=a^2+2ab+b^2\)